2002
DOI: 10.1152/ajplung.2002.282.1.l91
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidic acid upregulates the epidermal growth factor receptor in human airway smooth muscle cells

Abstract: Human airway smooth muscle cells treated with lysophosphatidic acid (LPA) and epidermal growth factor (EGF) exhibit synergistic stimulation of mitogenesis (Ediger TL and Toews ML. J Pharmacol Exp Ther 294: 1076-1082, 2000). The effects of LPA treatment of human airway smooth muscle cells on EGF receptor (EGFR) regulation have now been investigated. LPA treatment for 12-24 h resulted in a twofold increase in (125)I-EGF binding and EGFR protein levels as assessed by Western blot analysis. Competition binding ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
28
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 22 publications
5
28
1
Order By: Relevance
“…However, there is also some suggestion that "normal" stimuli such as bronchoconstrictor agonists (114,233,341) and other locally produced factors (5,53,75) could trigger increased proliferation under certain conditions, leading to the asthmatic phenotype. In this regard, interactions between GPCRs and RTKs may be important (18,67,68,155,162,303). For example, M 2 muscarinic receptors can potentiate TGF-␤-induced enhancement of proliferation (216).…”
Section: Asm In Airway Remodelingmentioning
confidence: 99%
“…However, there is also some suggestion that "normal" stimuli such as bronchoconstrictor agonists (114,233,341) and other locally produced factors (5,53,75) could trigger increased proliferation under certain conditions, leading to the asthmatic phenotype. In this regard, interactions between GPCRs and RTKs may be important (18,67,68,155,162,303). For example, M 2 muscarinic receptors can potentiate TGF-␤-induced enhancement of proliferation (216).…”
Section: Asm In Airway Remodelingmentioning
confidence: 99%
“…Because of the rapid time course in the epithelial cells, it is unlikely that the initial decrease in binding is a result of transcriptional inhibition of EGFR synthesis, but rather results from more rapid mechanisms such as transactivation, internalization, and perhaps degradation of EGFRs. Several studies have found that transactivation of the EGFR by LPA and other GPCR agents does not occur in HASM cells (Rakhit et al, 1999;Krymskaya et al, 2000;Ediger et al, 2002;Capra et al, 2003), and the lack of this response may be critical to the differences between regulation of EGFRs by LPA in epithelial versus mesenchymal cells. For both the differences among epithelial cell lines and the differences between epithelial versus mesenchymal cells, it is possible that one LPA receptor subtype and signaling pathway mediates one response, whereas a different subtype and signaling pathway mediates the other response.…”
Section: Lpa Regulation Of Airway Epithelialmentioning
confidence: 99%
“…ATX is present in plasma, saliva, follicular fluid, and malignant effusions (1,2). Through engagement with distinct high-affinity cell-surface G-protein-coupled receptors, LPA exhibits a wide range of effects on a variety of cell types, including bronchial epithelium, smooth muscle cells, fibroblasts, and lymphocytes (3)(4)(5). LPA augments cytokine synthesis and chemotaxis in lymphocytes (6)(7)(8)(9), induces contractility and proliferation of airway smooth muscle cells (10), and modulates inflammatory signaling in bronchial epithelial cells (10)(11)(12), suggesting a possible role in the molecular pathogenesis of asthma.…”
mentioning
confidence: 99%